Late settlements in the valley of the river Luren, middle basin of the Pancoy, Lucanas-Ayacucho - Sánchez Quispe, Kevin Jonatan (2021)
This article presents the preliminary results of archaeological surveys carried out in three communities belonging to the district of Aucará, Lucanas-Ayacucho: Pampamarca, Mayo Luren and Orccosa. The main objective is to characterize the pre-Hispanic occupations based on the architectural and spatial characteristics of the sites and, likewise, to approach the socio-political entity to which they would be linked during the Late Intermediate and Late Horizon Periods. The results show places of a residential nature, cemeteries and ceremonial spaces which would be cultural manifestations of the Lucanas Andamarca ethnic group, a pre-hispanic society originally from the south central region of Ayacucho.